High prevalence of Beijing and EAI4-VNM genotypes among M. tuberculosis isolates in northern Vietnam: sampling effect, rural and urban disparities. - Van Anh Thi Nguyen (Public Library of Science (PLoS), 2012)
A total of 221 isolates of M. tuberculosis were sampled from hospitals and the general population in the northern plain of Vietnam, one of the most populated region of the country. Genotypic composition and diversity were characterized, and we investigated how they are affected by sampling (hospital vs. general population), correcting for potential confounding effects (location, age and gender of the patients). Spoligotyping and 12 MIRU-VNTR typing were used as first line. Then 15 MIRU-VNTR standard set was used, making 21 MIRU-VNTR typing for the clustered isolates. Result showed that 8 lineages and 13 sub-lineages were circulating in the region. The most predominant lineages were Beijing (38.5%) and EAI (38.5%). Others appeared with small proportions H (1.4%), LAM (1.8%), T (8.1%), X (0.9%), MANU (2.3%), and Zero (0.4%). Higher clustering rate was found in the hospital samples (17.9% in urban and 19.2% in rural areas) compared to the population ones (0%). The typical Vietnamese EAI4-VNM sub-lineage of EAI lineage accounted for 67% of EAI strains and was associated with older ages. Beijing genotypes were associated with younger, urban population and were characterized by high clustering rates. These characteristics strongly suggest that Beijing strains are invading the population, replacing the local EAI-VNM4, thus predicting a more serious tuberculosis situation in the future in the absence of more effective control strategies.